Sustainability Strategy for Mangrove Forest Ecosystem Management in Ujung Baurung Coastal Area Majene Regency - Hermawan, Ade; Karim, Faradilah Farid (Pangale Journal of Forestry and Environment, 2021)
Mangrove ecosystems have extensive environmental benefits and services for humans and other living things. In addition to ecological benefits, mangrove forests also provide economic benefits for the community. Along with the increasing number and activity of the population, it has the potential to causes damage to mangrove forest and environmental degradation. This study aims to identify internal and external factors management of Ujung Baurung mangrove and to recommend mangrove sustainable management strategies. The analytical method used is SWOT analysis. The results showed that the highest internal factor that become the strength of Ujung Baurung mangrove management is the unique characteristics of the mangrove area, white sand and limestone cliffs. While, the internal factor that becomes a weakness is the lack of diversity in mangrove ecosystems. External factors that become opportunities are the regional regulations of West Sulawesi Province regarding the direction of developing beach and coastal tourism zones and the strategic location of the mangroves. The threat to its management include the existence of community activities taking mangroves for animal feed and household waste disposal to the mangrove forest. Management strategies recommendation, namely; spatial planning (zoning) ecotourism; maritime culture of Mandar Tribe as a tourist attraction; promoting Ujung Baurung mangrove as a unique natural resources area; and regulate and manage mangrove ecosystem areas by involving the community.